Lymphangiogenesis: from the pig embryos to cancer Linfangiogênese: de embriões de suínos ao câncer - Adhemar Longatto Filho; Maria Duarte; Fernando C. Schmitt (Sociedade Brasileira de Patologia Clínica, 2008)
The discovery and the comprehension of lymphatic vessels suffered several historical delays and setbacks. The inherent anatomical problems slowed down the precise identification of the lymphatic system during the development of medical science. Gasparo Aselli, an Italian surgeon and anatomist, was the first to describe the lymphatic vessels in 1627 (De Lacteibus sive Lacteis Venis). However, most original descriptions that report the morphology of the lymphatic system in different organisms were done during the 19th and the 20th centuries. The recent identification of specific lymphatic vasculature molecular markers allows a more accurate identification and characterization of the lymphatic system evolution in different organs, as well as its role in different pathological conditions, including cancer. This study summarizes the current understanding of lymphangiogenesis in tumour progression, as well as it presents a review of the promising data regarding the prognostic value of lymphatic density and the use of therapeutic lymphangiogenic molecules. A descoberta dos vasos linfáticos e sua compreensão enfrentaram uma série de atrasos e dificuldades históricos. As inerentes dificuldades anatômicas retardaram a identificação precisa da rede vascular linfática durante o desenvolvimento da ciência médica. Gasparo Aselli, um anatomista e cirurgião italiano, foi o primeiro a descrever os vasos linfáticos, em 1627 (De Lacteibus sive Lacteis Venis). Entretanto, a maioria das descrições originais que relatam a morfologia do sistema linfático nos diferentes organismos foi realizada depois, entre os séculos XIX e XX. A recente identificação de marcadores moleculares específicos à vasculatura linfática permite agora identificação e caracterização mais acuradas da evolução da rede linfática nos vários órgãos e em diferentes situações, inclusive no câncer. Esta revisão resume o conhecimento sobre a linfangiogênese na progressão tumoral, bem como apresenta uma síntese dos dados mais promissores em relação ao valor prognóstico da densidade linfática e da utilização das moléculas linfangiogênicas como alvo terapêutico.